IMPLIKASI YURIDIS UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP KORBAN DALAM SISTIM PERADILAN PIDANA TERPADU YANG BERKEADILAN GENDER - Nova, Efren; Elda, Edita (Universitas Ekasakti, 2022)
Sexual abuse is an act of violence and treatment that degrades human dignity, which is contrary to the values of God and humanity, and disturbs the security and tranquility of the social community. Handling victims of sexual abuse is very important, because the violence has caused various injuries to victims, such as fear, prolonged trauma, feelings of shame, evidentiary problems, repetitive questions by investigators, and the police investigations report process was not carried out properly so that it was difficult for the victim to recount the sexual abuse they experienced. If we look at many cases of violence against women and children, there are still no clear legal solutions. The promulgation of Law Number 12 of 2022 about sexual violence (UU TPKS), it is an effort to reform the law and overcome problems in legal protection of women and children from sexual abuse, namely as follows: preventing all forms of sexual violence, handling, protecting, and recovering victims, carry out law enforcement and rehabilitate perpetrators, create an environment where there is no sexual violence, and ensure non-repetition of sexual violence. Therefore, the problems statement in this research are: First, how are the regulation for the victims management of sexual violence based on Law Number 12 of 2022 about sexual violence (UU TPKS) and the Penal Code. Second, what are the juridical implications of the Law Number 12 of 2022 about sexual violence (UU TPKS) on victims in an Integrated Criminal Justice System that is gender-equitable. The problem approach in this study is a normative juridical, with data sources being the Criminal Procedure Code, the Penal Code, the Law Number 12 of 2022 about sexual violence (UU TPKS), Academic Papers on the Draft Law on the Elimination of Sexual Violence and other relevant sources. The results of the research show that the regulation of the Integrated Criminal Justice System in the UU TPKS regulated in Articles 20-64 is an effort to complement and strengthen the provisions on the rights of victims as regulated in existing laws and regulations. Meanwhile, the juridical implications of the UUTPKS for the Integrated Criminal Justice System are a guarantee of legal certainty, justice and the benefit of law in law enforcement of the Crime of Sexual Violence. A gender-just criminal justice system is one of the breakthroughs to change a non-gender-oriented legal system into a gender-oriented legal system. The system is expected to be able to respond to situations that are always experienced by women and children who are victims of gender-based sexual violence.